Engaging leadership: a step away from transformational leadership style in enhancing nurse educator’s job satisfaction in Malaysia - Moey, Soo Foon; Daud, Khadijah (2015)
The challenges confronting Malaysia’s nursing training colleges in their futuristic movement towards world class institutions are enormous. Among such challenges are job satisfaction and retention of nurse educators. As nursing education increases its complexity, leadership styles employed in these nursing training institutions play a crucial role in achieving nurse educators’ job satisfaction and onward staff retention. This paper examines the influence of transformational and transactional leadership style employed by nursing academic leaders on nurse educator’s job satisfaction and onward staff retention. This mix mode study using a cross sectional survey design and via focus group interview obtains data from nurse educators in the nursing colleges under MOH (Ministry of Health, Malaysia). The responses from the questionnaires were analysed using SEM (Structural Equation Modelling) while that of the qualitative aspect by using the software Atlas Ti. The findings indicated that transformational leadership played a highly significant role as well as a mediating role between transactional leadership style and nurse educators job satisfaction. A proposed model of effective academic nursing leadership uncovered effective leadership is enacted via engaging leadership where the engaging leader enables the development of an organization modelled by a culture of integrity, transparency, accessibility and genuine valuing of others and that their contributions is concerned for the development and well-being of others. This study has helped paved the way concerned in understanding the importance of leadership development and training to improve leadership qualities of nursing academic leaders.